Thermal imaging in plant and ecosystem ecology: applications and challenges. Issue 6 (11th June 2019) - Still, Christopher; Powell, Rebecca; Aubrecht, Donald; Kim, Youngil; Helliker, Brent; Roberts, Dar; Richardson, Andrew D.; Goulden, Michael
Abstract: Temperature is a primary environmental control on ecological systems and processes at a range of spatial and temporal scales. The surface temperature of organisms is often more relevant for ecological processes than air temperature, which is much more commonly measured. Surface temperature influences—and is influenced by—a range of biological, physical, and chemical processes, providing a unique view of temperature effects on ecosystem function. Furthermore, surface temperatures vary markedly over a range of temporal and spatial scales and may diverge from air temperature by 40°C or more. Surface temperature measurements have been challenging due to sensor and computational limitations but are now feasible at high spatial and temporal resolutions using thermal imaging. Thus, significant advances in our understanding of plant and ecosystem thermal regimes and their functional consequences are now possible. Thermal measurements may be used to address many ecological questions, such as the thermal controls on plant and ecosystem metabolism and the impact of heat waves and drought. Further advances in this area will require interdisciplinary collaborations among practitioners in fields ranging from physiology to ecosystem ecology to remote sensing and geospatial analysis. In this overview, we demonstrate the feasibility, utility, and potential of thermal imaging for measuring vegetation surface temperatures across a range of scales and from measurement, analysis, and synthesis perspectives.